Sazonalidade florística e fenologia em comunidades campestres no Parque Estadual de Vila Velha, Ponta Grossa, Paraná, Brasil - Micaloski, Laiane Maria (Universidade Estadual de Ponta Grossa, 2025)
Grassland formations are ecologically important yet increasingly threatened ecosystems, particularly in the Campos Gerais region of Paraná, southern Brazil. This study investigated the floristic composition, seasonal structure, and phenological patterns of grassland plant communities in three vegetation types within the Vila Velha State Park: dry grassland, wet grassland, and rocky grassland. The dissertation is organized into two chapters. The first chapter assessed floristic variation and seasonality from August 2023 to July 2024, considering species richness, functional structure, and temporal stability in relation to climate. Analyses included rarefaction, UPGMA (Sorensen index), stability, synchrony, turnover, and species rank. A total of 179 species across 46 families were recorded, with the dry grassland showing the highest richness. Asteraceae, Poaceae, and Fabaceae accounted for 52% of the flora. Hemicryptophytes were dominant (55%), and anemochory was the most common dispersal syndrome, especially in the dry grassland. Thirty-two species are nationally threatened, and eleven are listed at the state level. The dry grassland had the highest species diversity, with a continuously increasing rarefaction curve. UPGMA analysis indicated strong differentiation among the vegetation types. The wet grassland showed greater stability, while the dry grassland exhibited lower synchrony and higher turnover. Annual precipitation totaled 1078 mm, with 29% concentrated in October followed by nine months of drought, coinciding with species disappearance and recruitment, particularly in the dry grassland. The second chapter compared phenological events from July 2012 to July 2013 and from 2023 to 2024 using the Fournier index and Spearman correlations with climate data. In 2023–2024, flowering and fruiting were longer and less synchronized, especially in the dry grassland. In 2012–2013, peak events occurred later. The interaction between temperature and precipitation was strongly correlated with flowering in the dry grassland, and senescence occurred earlier in the dry and rocky grasslands. The results indicate changes in phenological patterns over the past decade, linked to climate change. The findings highlight the park’s high grassland diversity, with variable ecological stability among vegetation types, emphasizing the vulnerability of dry grasslands and the need for continuous monitoring, adaptive management, conservation efforts, and further studies on local flora.
Keywords: Vegetação campestre; Fenologia; Sazonalidade; Composição florística; Mudanças climáticas